(untitled) (Journal of the College of Education for Women, 2019)
In her poetry, Carol Ann Duffy looks into the concerns of the disregarded and humiliated people. Approaching facts fearlessly and disclosing realities in a way highly characteristic of her, she establishes the world newly and reframes it honestly. This research shows how Duffy reframes the world in her own peculiar terms, starting with her own creative use of the language, in particular, when the forms of things of the world are distorted, thus our perception of things will be reframed too.As regards relations among people, the research elucidates how Duffy’s strained characters abandon real life and reframe an eccentric way of living, while respecting faith, wherein Duffy notices that religious rituals confine the intellect, she reframes them by adopting the secular and familiar rather than the sacred and ceremonial. The hideousness of war is another motif in her poetry where she pervertedly reframes the entity and wholesomeness of the victims of war in order to leave us reflect on the tragedy of war. Duffy also challenges the misconceptions of adults about childhood, and she cleverly reframes the relationship between adults and children. Lastly, the research puts forth the subject of time and memory where her characters reframe a sense of satisfaction through mental mechanisms in order to adapt themselves to the vicissitudes of time. The research concludes that Duffy stands lofty, contemplating and suggesting extraordinary solutions for incurable problems.